SAT0085 The Role of Vitamin D and Disease Activity in Rheumatoid Arthritis Pacients. (23rd January 2014) - Stoica, S.; Zugravu, G.
Abstract : Background: Vitamin D plays an important role in immune regulation. There are a lot of studies which prove that vitamin D deficiency may be a risk for development of autoimmune diseases [1, 3, 6]. Preliminary studies suggest that low levels of vitamin D may be common in rheumatoid arthritis (RA) [2, 5, 7]. Objectives: The aim of this study is to estimate the prevalence of vitamin D deficiency in patients with RA, and to analyze the association of vitamin D with disease activity and disability. Methods: The study includes 52 RA premenopausal women aged between 35- 48 years, 32, 7 % (17 pacients) with vitamin D supplements. Clinical evaluation included: disease onset and duration, presence of extraarticular manifestations, 28 tender joint count (TJC28) and 28 swollen joint count (SJC28), Disease Activity Score (DAS 28) was calculated using C-reactive protein (CRP), Health Assessment Questionnaire Disability Index (HAQ). RA specific treatment included the glucocorticoids, disease modifying antirheumatic drugs (DMARDs: methotrexate, cyclosporine, sulfasalazine, antimalarials, and azathioprine) and biologic therapy (anti-TNF or no). Exposure to sunlight from March to September (sun exposure time) was quantified as <10, 10 to 20, 20 to 30 or >30 minutes daily. Laboratory assessment included: rheumatoid factor (RF), anti Cyclic Citrullinated Peptide (anti-CCP), routine biochemistry, CRP, ESR and 25(OH)D level (25(OH)D level <30 ng/ml was considered as vit D deficiency). Results: A total of 67, 3 % of RA patients were not taking vitamin D supplements; the proportion of these with vitamin D deficiency (25(OH)D level <30 ng/ml) was 68%. In non-supplemented RA patients, 25(OH)D levels were negatively correlated with the Health Assessment Questionnaire Disability Index, Disease Activity Score (DAS28). In patients not taking vitamin D supplements, a significant negative correlation between 25(OH)D serum levels and age was observed ( P < 0.05), and mean values from June to December were significantly higher than from January to May (24.5 versus 18.0 ng/ml, respectively). Significantly lower 25(OH)D values were found in patients not experiencing disease remission or with DAS28 >5.1 or poorlyresponding to treatment. Vitamin D deficiency was found in 56% of the entire cohort. Conclusions: Vitamin D deficiency is common in RA patients. Patients with very active disease are at higher risk of vitamin D deficiency rather than the other. Patients with uncontrolled RA and/or with severe functional impairment are less prone to spend time outdoors in sunshine and are, therefore, at higher risk of vitamin D deficiency. References: Holick MF: Vitamin D deficiency N Engl J Med 2007, 357:266-281. PubMed Abstract Holick MF: Sunlight and vitamin D for bone health and prevention of autoimmune diseases, cancers, and cardiovascular disease. Am J Clin Nutr 2004, 80:1678S-1688S. PubMed Abstract Jones G, Strugnell SA, DeLuca HF: Current understanding of the molecular actions of vitamin D. Physiol Rev 1998, 78:1193-1231. PubMed Abstract Arnson Y, Amital H, Shoenfeld Y: Vitamin D and autoimmunity: new aetiological and therapeutic considerations Ann Rheum Dis 2007, 66:1137-1142. PubMed Abstract Disclosure of Interest: None Declared